Enterprise file synchronization and sharing services for educational environments in case of disaster - Delgado Domínguez, Ana Isabel; Fuertes Díaz, Walter Marcelo; Sánchez Gordon, Sandra Patricia (Universidad Pedagógica y Tecnológica de Colombia, 2018)
1 recurso en línea (páginas 81-91).